The role of urocortins in intracerebral hemorrhage - Choy K.W.; Tsai A.P.-Y.; Lin P.B.-C.; Wu M.-Y.; Lee C.; Alias A.; Pang C.-Y.; Liew H.-K. (MDPI AG, 2024)
Intracerebral hemorrhage (ICH) causes an accumulation of blood in the brain parenchyma that disrupts the normal neurological function of the brain. Despite extensive clinical trials, no medical or surgical therapy has shown to be effective in managing ICH, resulting in a poor prognosis for the patients. Urocortin (UCN) is a 40-amino-acid endogenous neuropeptide that belongs to the corticotropin-releasing hormone (CRH) family. The effect of UCN is activated by binding to two G-protein coupled receptors, CRH-R1 and CRH-R2, which are expressed in brain neurons and glial cells in various brain regions. Current research has shown that UCN exerts neuroprotective effects in ICH models via anti-inflammatory effects, which generally reduced brain edema and reduced blood-brain barrier disruption. These effects gradually help in the improvement of the neurological outcome, and thus, UCN may be a potential therapeutic target in the treatment of ICH. This review summarizes the data published to date on the role of UCN in ICH and the possible protective mechanisms underlined.